Mental Distress Damages for Breach of Contract - Holmes, Renee (Victoria University of Wellington Law Review, 2004)
The common law has long held that damages for the mental distress suffered after a breach of contract are unrecoverable. Like all rules, a range of exceptions has developed to mitigate the severity of this rule. In this article the author argues that both the rule and its exceptions, being based neither in principle nor sound policy, have only created confusion in the law. The decision of the House of Lords in Farley v Skinner is analysed as a possible solution to this confusion, but is found to be unhelpful. The author concludes by calling for a principled revision of this area of the law in accordance with the usual principles of damages.